Genetic and epigenetic studies in non‐syndromic oral clefts. (27th February 2022) - Alade, Azeez; Awotoye, Waheed; Butali, Azeez
Abstract: The etiology of non‐syndromic oral clefts (NSOFC) is complex with genetics, genomics, epigenetics, and stochastics factors playing a role. Several approaches have been applied to understand the etiology of non‐syndromic oral clefts. These include linkage, candidate gene association studies, genome‐wide association studies, whole‐genome sequencing, copy number variations, and epigenetics. In this review, we shared these approaches, genes, and loci reported in some studies.